Quality improvement in randomized controlled trial abstracts in prosthodontics since the publication of CONSORT guideline for abstracts: A systematic review. (July 2018) - Chen, Junsheng; Li, Zhi; Liu, Beilei; Gan, Xueqi; Li, Chunjie; Yu, Haiyang
Abstract: Objectives: This study aimed to compare the reporting quality of randomized controlled trial (RCT) abstracts in prosthodontics before and after the publication of Consolidated Standards of Reporting Trials (CONSORT) guideline for abstracts and identify the characteristics associated with better reporting quality. Sources: PubMed was searched for RCT abstracts published from 2001 to 2007 (pre-CONSORT period) and from 2010 to 2016 (post-CONSORT period) in six leading prosthodontic journals. Study selection: After applying the inclusion/exclusion criteria, 131 RCT abstracts were selected. The t test was performed to compare the overall quality between the two periods. Univariable and multivariable linear regressions were used to identify any factors relating to the reporting quality. The level of significance was set at P < 0.05. Data: The investigators extracted data and scored the abstracts independently based on CONSORT. The mean overall CONSORT score was 5.20 and 6.11 in the pre- and post-CONSORT samples, respectively. Significant changes were observed in reporting for only three items: title, conclusions, and trial registration. Most abstracts adequately reported interventions, objectives, and conclusions (>90%), but failed to report recruitment and outcome in the results section (<3%). Funding was not reported in both periods. The reporting quality was related to a higher impact factor, structured format, and published after CONSORT. Conclusions: The quality of RCT abstracts in prosthodontics improved over time, but adherence to the CONSORT guideline for abstracts was still suboptimal.